Handwriting Declines With Human Aging: A Machine Learning Study - Asci, Francesco; Scardapane, Simone; Zampogna, Alessandro; D’Onofrio, Valentina; Testa, Lucia; Patera, Martina; Falletti, Marco; Marsili, Luca; Suppa, Antonio (Frontiers in Aging Neuroscience, 2022)
Background: Handwriting is an acquired complex cognitive and motor skill resulting from the activation of a widespread brain network. Handwriting therefore may provide biologically relevant information on health status. Also, handwriting can be collected easily in an ecological scenario, through safe, cheap, and largely available tools. Hence, objective handwriting analysis through artificial intelligence would represent an innovative strategy for telemedicine purposes in healthy subjects and people affected by neurological disorders. Material and Methods: One-hundred and fifty-six healthy subjects (61 males; 49.6±20.4 years) were enrolled and divided according to age into three subgroups: younger adults (YA), middle-aged adults (MA), and older adults (OA). Participants performed an ecological handwriting task that was digitalized through smartphones. Data underwent the DBNet algorithm for measuring and comparing the average stroke sizes in the three groups. A convolutional neural network (CNN) was also used to classify handwriting samples. Lastly, receiver operating characteristic (ROC) curves and sensitivity, specificity, positive, negative predictive values (PPV, NPV), accuracy and area under the curve (AUC) were calculated to report the performance of the algorithm. Results: Stroke sizes were significantly smaller in OA than in MA and YA. The CNN classifier objectively discriminated YA vs. OA (sensitivity=82%, specificity=80%, PPV=78%, NPV=79%, accuracy=77%, and AUC=0.84), MA vs. OA (sensitivity=84%, specificity=56%, PPV=78%, NPV=73%, accuracy=74%, and AUC=0.7), and YA vs. MA (sensitivity=75%, specificity=82%, PPV=79%, NPV=83%, accuracy=79%, and AUC=0.83). Discussion: Handwriting progressively declines with human ageing. The effect of physiological ageing on handwriting abilities can be detected remotely and objectively by using machine learning algorithms.